Nitrous oxide emission from excreta of different beef cattle breeds finished in feedlot - Teixeira, Natalia Pinheiro; Oliveira, Alan Figueiredo de; Menezes, Guilherme Lobato; Alvarenga, Ramon Costa; Campanha, Mônica Matoso; Alves, Bruno José Rodrigues; Lana, Ângela Maria Quintão (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to compare nitrous oxide (N2O) emissions from urine and manure of Nellore and crossbred (Nellore x Angus) cattle finished in feedlot. Twenty Nellore and 20 crossbred bulls were fed a diet consisting of 75% concentrate and 25% roughage. Excreta were applied to the pens after 43 days of confinement, when N2O monitoring started through static chambers. The data were subjected to the analysis of variance, and averages were compared by Tukey’s test. The N2O fluxes from urine and manure were similar among the breeds, with important peaks after rain events. The cumulative emissions of N2O from urine per kilogram of body weight gain (BWG) and the total emissions from manure per kilogram of BWG were 22.7% and 24.4% higher in Nellore cattle. There is no breed effect on N2O flux and cumulative emissions by excreta from confined beef cattle; however, the crossbreed emits less per kilogram of BWG. There is a high correlation between rainfall volume and the N2O emissions of the next day, which indicates a period between rain occurrence and the increase in N2O emission.